Risk analysis of Odelouca cofferdam - Pimenta, L. (2009)
In this paper we present the risk analysis of Odelouca Cofferdam, using an event tree analysis. The initializing events, failure modes and analysed limit states are discussed based on an influence diagram. The constructed event trees and their interpretation are presented. The obtained risk values are represented in an FN plot superimposed to the acceptability and tolerability risk limits proposed for Portuguese dams. Initially, particular emphasis is placed on the main characteristics of the cofferdam and deviation hydraulic structures, as well as on some important construction aspects conditioning the expected structural behaviour and the analysed limit states. Downstream valley characteristics and the results of dam break studies, which based the consequences identification and evaluation, are also present.